Participation‐focused practices in paediatric rehabilitation for children with neurodisability in New Zealand: An observational study using MAPi audit tool. (23rd June 2020) - Graham, Fiona; Timothy, Emily; Williman, Jonathan; Levack, William
Abstract: Background: Participation outcomes and family‐centred services are now widely agreed standards of care in paediatric rehabilitation. Evidence suggests that adoption of these practices into usual care has been slow internationally, and no studies of participation‐focused or family‐centred practices in New Zealand have been undertaken to date. The aims of this study were to identify the extent that goal setting in paediatric rehabilitation services is participation focused and family centred and to profile clinicians' beliefs about these foci. Methods: Observational study including a retrospective case note audit and questionnaire. Case notes ('charts') were audited for participation‐focused goal‐related practice. Subgroup analysis of audit data by service, profession and child ethnicity were completed using weighted mean differences. Clinicians whose case notes were audited completed a 42‐item questionnaire on factors related to practice behaviour including text responses with each item. Numerical and text data were analysed descriptively. Results: Five services were recruited ( N = 46 clinicians) with case notes for 220 children audited. Auditors extracted 368 potentially participation‐related goals ( Mdn = 2 goals per child) with no goals extracted for 43 (20%) of case notes. Subsequent coding of extracted goals identified 61% reflected participation (225/368). Subgroup analysis revealed significant differences between services ( p = 0.006) and professions ( p < 0.001). Clinicians' reported valuing participation outcomes and family involvement and largely felt they did target participation. Skill gaps, absence of self‐monitoring strategies and unsupportive professional and work cultures were cited as key challenges. Conclusions: Although valued by clinicians, participation‐focused practice is unusual care in paediatric rehabilitation in New Zealand. Substantial gains in the quality of care for children with disabilities could be afforded through training in collaborative goal setting to target participation outcomes.